EVALUASI PASCA HUNI ASPEK FUNGSIONAL PUSKESMAS PAL III KOTA PONTIANAK - Amalia, Laili Rizki; Nurhamsyah, Muhammad; Lestari, Lestari (JMARS: Jurnal Mosaik Arsitektur, 2021)
Community health center also known as Puskesmas are public healthcare facilities located across Indonesia. Puskesmas Pal III is a community health center in Pontianak which has been established and operating since 1993. A re-evaluation is required to adjust current building condition to users needs, standards, and regulations. The re-evaluation is also known as post occupancy evaluation (POE). This study uses mixed methods (qualitative and quantitative) which compare the questionnaire results from building users as respondents to theories and standards regarding Community Health Center or health facilities in general. In the process, the data analysis using this method is connected by three functional aspect variables namely zoning and layout, circulation, and dimensions. The result of the study shows that the spaces in Puskesmas Pal III have been operating properly according to its function, the relationship between spaces is considered quite comfortable and have met the minimum standard also grouped based on the same function, and the circulation in the building is also considered comfortable. Moreover, from samples that have been studied, the space layout is considered quite spacious although there is an inadequate space which is over capacity in motorcycle parking areas for visitors.